Electrochemical and thermodynamic investigation of nitrofurantoin as effective corrosion inhibitor for mild steel in 1M hydrochloric acid solution - Reddy M.J.; Verma C.B.; Ebenso E.E.; Singh K.K.; Quaraishi M.A. (My University, 2025)
In present study corrosion inhibition property of (E)-1-[(5-nitro-2furyl) methylideneamino] imidazolidine-2, 4-dione (Nitrofurantoin) in 1M HCl was investigated using weight loss, electrochemical impedance spectroscopy and potentiodynamic polarization, SEM and EDX techniques. From weight loss and electrochemical measurements it is observed that inhibition efficiency increases with Nitrofurantoin concentration and maximum efficiency (97.6) was obtained at 50 ppm. The potentiodynamic study reveals that Nitrofurantoin is a mixed type inhibitor. Adsorption of Nitrofurantoin on mild steel surface obeys the Langmuir adsorption isotherm. The morphology of the surface was examined by scanning electron microscopy (SEM), and the surface composition was evaluated using energy-dispersive X-ray spectroscopy (EDX) to verify the presence of Nitrofurantoin on the mild steel surface. The effect of temperature on the corrosion rate was investigated and some thermodynamic parameters were also calculated in order to explain the mechanism of adsorption. © 2014 The Authors.